A primal heuristic for the routing and spectrum assignment problem - Bianchetti, Marcelo (2021)
In this work we propose a primal heuristic to improve the branch-and-cut algorithm presented in for one of the ILP formulations of the RSA problem proposed in, namely, the model DSL-BF.